A new species of Lepidotrigona (Hymenoptera: Apidae) from Thailand with the description of males of L. flavibasis and L. doipaensis and comments on asymmetrical genitalia in bees - Attasopa, Korrawat; Bänziger, Hans; Disayathanoowat, Terd; Packer, Laurence (Zootaxa, 2018)
We describe Lepidotrigona satun Attasopa and Bänziger new species from southern Thailand based upon associated males and females (workers). The new species is a member of the L. ventralis species group, which is otherwise represented in Thailand only by L. flavibasis and L. doipaensis. We also describe the males of the latter two species, associated with nests from close to their type localities in northern Thailand. Lepidotrigona doipaensis Schwarz and L. flavibasis (Cockerell) had previously often been misidentified as L. ventralis (Smith), a species confirmed only from Borneo. Based upon differences in male morphology, especially of the metasomal sterna, we conclude that the male described from Vietnam by Sakagami (1975) as belonging to L. flavibasis represents an undescribed species. Our findings support previous taxonomic studies that highlight the importance of including males in the differentiation of closely related species of meliponines and their association with workers. The three species whose males we describe have asymmetric penis valves with the asymmetry differentially developed among the three. We compare this genitalic asymmetry with that known from a different apid genus, Tarsalia.